Gum Arabic-assisted green synthesis of gold nanoparticles as fluorescence modulator for potential analytical applications - Ahmed T. Algahiny; Omar S. Elmitwalli; Deyari A. Kassim; G. Roshan Deen; Sultan Akhtar; Fryad Z. Henari (Exploration of BioMat-X)
Aim: To demonstrate a simple, eco-friendly, and cost-effective green method to synthesize gold nanoparticles (AuNPs) using the aqueous extract of gum Arabic (GA) as a reducing and stabilizing agent. Methods: Green synthesis of nanoparticles, characterization by absorption, infra-red and fluorescence spectroscopy. Results: The absorption spectrum (UV-Vis) showed an absorption peak ~522 nm corresponding to the surface plasmon resonance (SPR) absorption peak of AuNPs. Transmission electron microscopy (TEM) images revealed spherical-shaped nanoparticles with an average size of 15 nm. Fourier transform infrared (FTIR) analysis showed that the nanoparticles are coated with organic compounds that are present in GA. The fluorescence quenching properties of the AuNPs were assessed by monitoring their effects on fluorescence intensity of coumarin 153 (C153) dye. The fluorescence of the dye decreased with an increase in concentration of the nanoparticles. Upon addition of the protein bovine serum albumin (BSA) to the mixture the fluorescence increased (recovery) again. Conclusions: The fluorescence quenching and recovery (turn-on/off system) is a valuable method for protein detection in solution. By observing the effect of BSA on the quenched fluorescence, this nanoparticle system shows promise in biomedicine, drug delivery and environmental monitoring.